2021
DOI: 10.1111/1750-3841.15780
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of protein fractions from chia (Salvia hispanica L.)

Abstract: Salvia hispanica demonstrated to be a source of protein fractions with anticancer activity. The effect of the protein fractions <1, 1–3, and 3–5 kDa, obtained by ultrafiltration of the S. hispanica hydrolysate, was evaluated on the cellular viability of four cancer cell lines (MCF‐7, Caco2, PC‐3, and HepG2) and on human fibroblasts (hFB) at different concentrations (0.25, 0.5, 0.75, and 1 mg/ml). The protein fractions did not show cytotoxic effects on hFB. The protein fraction <1 kDa at 1 mg/ml showed the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
2
6
0
1
Order By: Relevance
“…In a model of mammary gland adenocarcinoma in mouse, Espada et al 24 investigated the effects of Carthamus tinctorius and Salvia hispanica oil on eicosanoid synthesis, growth, and metastasis. In the present study, the aqueous extract of Chia seeds crude inhibited cell proliferation and induced apoptotic cell death of the cancer cell lines, Quintal-Bojórquez et al 25 demonstrated that the present low molecular weight peptides , obtained from chia seeds, as a potential adjuvant option for treatment of cancer.…”
Section: Discussionsupporting
confidence: 53%
“…In a model of mammary gland adenocarcinoma in mouse, Espada et al 24 investigated the effects of Carthamus tinctorius and Salvia hispanica oil on eicosanoid synthesis, growth, and metastasis. In the present study, the aqueous extract of Chia seeds crude inhibited cell proliferation and induced apoptotic cell death of the cancer cell lines, Quintal-Bojórquez et al 25 demonstrated that the present low molecular weight peptides , obtained from chia seeds, as a potential adjuvant option for treatment of cancer.…”
Section: Discussionsupporting
confidence: 53%
“…Seed mucilages may reduce the risk of colon cancer and rectal cancer, and could help protect against coronary heart diseases [76]. Salvia (sage), from the family Lamiaceae, comprises about 1000 species and is wellrecognized for its medical, food, and feed applications [77]. Two species of sage-Salvia hispanica and S. macrosiphon-have attracted the greatest interest from researchers and industry.…”
Section: Application Of Plant-derived Mucilagementioning
confidence: 99%
“…Karami, Peighambardoust, Hesari, Akbari‐Adergani, and Andreu ( 2019a ) also reported that wheat germ protein hydrolysates obtained by alcalase, pepsin, or proteinase K had significant antioxidant activities and the ability to decrease A549 cell viability in a concentration‐dependent manner. In a very recent study, anticancer activity and apoptotic potential of pepsin and pancreatin polypeptides from chia ( Salvia hispanica ) protein (Quintal‐Bojórquez et al, 2021 ) and pepsin hydrolysates from Amaranthus cruentus protein (Ramkisson et al, 2020 ) were proven.…”
Section: Resultsmentioning
confidence: 99%